Successful selling of packed fresh fruit and vegetable - Radmila Presová; Oldřich Tvrdoň; Lucie Hrdá (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2009)
The paper deals with the marketability of packaged fruit and vegetables, as a new trend of satisfying consumer needs, in connection with selling-culture of stall selling and self-stores sales. It emphasize fact that food have to be wrapped into the quality, health packages, under the conditions of the Act. 477/2001 Coll.Specific data for the analytical part of this paper was provided by Hortim International Ltd. This company has operate on the Czech market since 1995. Analysis of the economic results confirmes the legitimacy of the sale of packaged fresh fruits and vegetables, but there will be neccesary longer lasting promotion. This fact also confirmed the research of consumer demand, that was made by authors. Determinant for the success sales are these factors: consumer confidence that the packaged products of fruit and vegetables are high quality.